2014
DOI: 10.1007/s10549-014-3042-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cost-effectiveness analysis of everolimus plus exemestane versus exemestane alone for treatment of hormone receptor positive metastatic breast cancer

Abstract: Everolimus in combination with exemestane significantly improved progression-free survival compared to exemestane alone in patients previously treated with non-steroidal aromatase inhibitors in the BOLERO-2 trial. As a result, this combination has been approved by the food and drug administration to treat postmenopausal women with hormone receptor positive and HER2 negative metastatic breast cancer. A cost-effectiveness analysis was conducted to determine whether everolimus represents good value for money, uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…14.4% of the discontinuations were up to patients’ choice, mainly because of economic pressure. A cost-effective analysis based on the results of BOLERO-2 shows that the total cost of everolimus/exemestane ($63,584) was 21 times higher than the cost of exemestane alone ($3,010) [ 23 ]. Since everolimus hasn't been covered up by Chinese health insurance, it makes sense that people might find it unable to afford.…”
Section: Discussionmentioning
confidence: 99%
“…14.4% of the discontinuations were up to patients’ choice, mainly because of economic pressure. A cost-effective analysis based on the results of BOLERO-2 shows that the total cost of everolimus/exemestane ($63,584) was 21 times higher than the cost of exemestane alone ($3,010) [ 23 ]. Since everolimus hasn't been covered up by Chinese health insurance, it makes sense that people might find it unable to afford.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in asymptomatic luminal patients with good prognosis, the combination treatment should be comparable to the HT alone in terms of toxicity to ensure the maintenance of good clinical conditions. Cost-effectiveness analysis demonstrated conflicting results on everolimus plus exemestane compared to exemestane alone in BOLERO-2 [ 20 ]. Long-term results and analysis of post-marketing studies are indeed needed to finally address this important issue.…”
Section: Discussionmentioning
confidence: 99%
“…Overview of cost studies Findings on costs were reported by three articles [50][51][52] and two conference abstracts (Table 7) [53,54]. These studies varied in aims, designs, data sources and therapies: for example, three were cost-effectiveness analyses [50,51,54], one study was a budget impact model [52] and one study was a retrospective secondary database analysis [53].…”
Section: Overview Of Qol Researchmentioning
confidence: 99%
“…These studies varied in aims, designs, data sources and therapies: for example, three were cost-effectiveness analyses [50,51,54], one study was a budget impact model [52] and one study was a retrospective secondary database analysis [53]. All patients examined were women with HER-negative mBC.…”
Section: Overview Of Qol Researchmentioning
confidence: 99%
See 1 more Smart Citation